Evaluation of The Factors Affecting the Benefiting Level from The Young Farmers Project Support in TR 71 Region of Turkey - Hasan Gökhan Doğan; Arzu Kan; Mustafa Kan; Fatma Tosun; İlkay Uçum; Cengiz Solmaz; Duygu Birol (Turkish Journal of Agriculture: Food Science and Technology)
In Turkey, various agricultural support policies were applied some time to increase the production, sometimes to reduce the over-production and to compensate the production. However, these policies have not been fully attained since they have been implemented without first solving the major structural problems of agriculture. Parallel to developments in the world's countries, entrepreneurship needs to be embraced by the young population and young entrepreneurs must be supported. Turkey attaches great importance to the supports in recent years regarding the determination of entrepreneurial individuals, and the promotion of entrepreneurship. For this purpose, in order to support young people in the agriculture sector, "Young Farmer Projects Support (YFPS)" was added to the "National Agricultural Project" in 2016. This support policy aims to encourage young farmers to stay in agriculture by supporting young farmers and to prevent migration from the village to the city. In this context, a survey has been carried out in the TR 71 Region of Turkey (Aksaray, Kırıkkale, Kırşehir, Nevsehir and Nigde provinces), and a total of 248 young farmers (139 supported, and 109 non-supported) were interviewed. The logit model was used in the analysis of the data. According to Logit model results, the factors such as gender, marital status, farming situation of young farmer, farming situation of young farmer’s family, residence population, social security status, agricultural education certificate status and ownership of property which are influencing on individuals benefiting from young farmer support were found statistically significant.